Productivity of newly released common bean (Phaseolus vulgaris L.) varieties under sole cropping and intercropping with maize (Zea mays L.) - Nkhata, W.; Shimelis, Hussein; Chirwa, R. (Frontiers Media, 2021)
Intercropping maize (Zea mays L.) with common bean (Phaseolus vulgaris L.) is one of the predominant farming practices in eastern and southern Africa (ESA) for effective use of resources and continuous household food supply. The productivity of sole or intercropped crops is subject to variety, location, year, and their interaction. Therefore, the objective of this study was to determine the productivity of newly released common bean varieties NUA45 and SER83 under sole cropping and intercropping with a maize hybrid variety SC672 as a guide to large-scale production. Experiments were conducted at Chitedze Agricultural Research Station (13.85°S; 33.38°E) and Linthipe Extension Planning Area (12.06°S; 33.25°E) in 2019 and 2020 in Malawi using a factorial arrangement laid out in a randomized complete block design (RCBD) with four replications. The numbers of pods per plant (NPP) and seeds per pod (NSP), grain yield (GYD), and 100-seed weight were collected for common bean included, while GYD was recorded for maize. The main effects for genotype, location, year, and intercropping system were significant (p < 0.05) for GYD in common bean. The effects of the year and cropping system and location by intercropping system interaction were significant for maize GYD. The maize yield did not vary between sole cropped and intercropped systems. The total land equivalent ratios (LERs) for NUA45 and SER83 were 1.59 and 1.77, respectively. The LER-values showed a significant difference (p < 0.034), suggesting a considerably higher benefit of maize and common bean intercropping. Overall, intercropping maize with common bean rendered higher yields in the SER83/SC672 intercropping system than the sole crop in the study areas. Therefore, intra-row intercropping of the newly released common bean variety SER83 with a maize hybrid variety SC672 is recommended in the study area and other similar agro-ecologies for stable and sustainable production of both crops.